Aromatase inhibitors: the journey from the state of the art to clinical open questions - Generali, Daniele; Berardi, Rossana; Caruso, Michele; Cazzaniga, Marina; Garrone, Ornella; Minchella, Ida; Paris, Ida; Pinto, Carmine; De Placido, Sabino (Frontiers in Oncology, 2023)
Breast cancer is a major cause of death among females. Great advances have been made in treating this disease, and aromatase inhibitors (AIs) have been recognized as the cornerstone. They are characterized by high efficacy and low toxicity. The authors reviewed the available literature and defined state-of-the-art AIs management. This study was designed to assist clinicians in addressing the need to equally weigh patients' needs and disease control rates in their everyday clinical practice. Today, AIs play a central role in the treatment of hormone-receptor-positive breast cancer. In this study, an expert panel reviewed the literature on the use of AIs, discussing the evolution of their use in various aspects of breast cancer, from pre- and postmenopausal early breast cancer to metastatic breast cancer, along with their management regarding efficacy and toxicity. Given the brilliant results they have achieved in improving survival in everyday clinical practice, clinicians need to address their concerns about therapy duration and the adverse effects they exert on bone health, the cardiovascular system, and metabolism. Currently, in addition to cancer treatment, patient engagement is crucial for improving adherence to therapy and supporting patients’ quality of life, especially in a selected subset of patients, such as those receiving an extended adjuvant or combination with target therapies. A description of modern technologies that contribute to this important goal is provided.